Photoelectrocatalytic/photoelectro-Fenton coupling system using a nanostructured photoanode for the oxidation of a textile dye: kinetics study and oxidation pathway - Almeida, Lucio C. [UNESP]; Silva, Bianca F. [UNESP]; Zanoni, Maria V. B. [UNESP] (Elsevier B. V., 2015)
In this study, a coupled photoelectrocatalytic/photoelectro-Fenton reactor was designed to enhance the degradation efficiency of organic pollutants and tested using the azo dye Orange G as a model compound. Pt-decorated TiO2 nanotubes were used as a photoanode with an air-diffusion polytetrafluoroethylene cathode for H2O2 generation. The sum of individual effects of coupling the photoelectrocatalytic and photoelectro-Fenton processes was evaluated as a function of the decolorization and mineralization of Orange G solutions. The dye solutions were only completely decolorized in more acidic conditions (pH 3.0). The mineralization of the Orange G solutions increased in the sequence photoelectrocatalytic<electro-Fenton<coupled photoelectrocatalytic/photoelectro-Fenton due to the gradual increase in the production of OH radicals. Total organic carbon reductions of 80% for photoelectrocatalysis, 87% for electro-Fenton and 97% for the coupled processes were obtained when using an applied electric charge per unit volume of electrolyzed solution of 200 mA h L(-1). The Orange G decays for all treatments followed pseudo-first-order kinetics, suggesting the attack of a constant concentration of OH radicals. Aromatics such as naphthalenic and benzenic compounds were formed as by-products and were identified using LC-MS/MS analysis. In addition, the generated aliphatic acids were identified using ion-exclusion high-performance liquid chromatography. The final by-products of oxalic and formic acid were identified as ultimate by-products and formed Fe(III) complexes that were rapidly mineralized to CO2 by UV-Vis irradiation. Then, according to the identified oxidation by-products, a plausible pathway was proposed for the degradation of Orange G dye by the coupled process.
Keywords: Dye degradation pathway; Photoelectro-fenton; Photoelectrocatalysis; Pt-decorated tio(2)nt anode; Wastewater treatment